Regional Language Studies. Newfoundland, Number 01 (1 October 1968) - Kirwin, William J., 1925- (William James) (Memorial University of Newfoundland. Department of English Language and Literature, 1968)
The present state of language studies in Newfoundland -- Bibliography of writings on Newfoundland English -- Either for any in Newfoundland / W. Kirwin -- Linguistic research materials in the Folklore Archive at Memorial University.